IgE sero-positivity to 27 Culicoides recombinant (r-) allergens. - Jasmin Birras (11707271); Samuel J. White (10512181); Sigridur Jonsdottir (1303788); Ella N. Novotny (11707274); Anja Ziegler (11707277); A. Douglas Wilson (11707280); Rebecka Frey (3362939); Sigurbjörg Torsteinsdottir (11707283); Marcos Alcocer (8212260); Eliane Marti (157764) (2021)
Percentage of horses with IgE levels above the cut-off values (as indicated in Table 2 ) in horses exported from Iceland to Switzerland that developed insect bite hypersensitivity (IBH; n = 59) or remained healthy (H; n = 51), and in horses living in Iceland (unexposed; n = 22). Serum samples were taken the summer of clinical onset of IBH (T IBH ) and at the corresponding time in the H group. The allergens are listed in decreasing order from those binding serum IgE in the highest number of horses at time of clinical onset of IBH (T IBH ). P values were calculated with the Fisher’s exact test and Bonferroni correction done for multiple comparisons. ** IBH significantly different from H and unexposed (cP <0.05). * IBH significantly different from H (cP<0.05). No significant differences between H and unexposed for any r-allergen.